Was there really any evidence that rosiglitazone increased the risk of myocardial infarction or death from cardiovascular causes?. (16th December 2014) - Stone, Jennifer C.; Furuya‐Kanamori, Luis; Barendregt, Jan J.; Doi, Suhail A. R.
Abstract: Rosiglitazone has previously been widely used to treat patients with type 2 diabetes mellitus, but its safety in terms of cardiovascular morbidity and mortality had been called into question. Recently, there have been doubts raised about the meta‐analytic evidence with the regulatory authorities relaxing its restrictions. We hypothesized that the original analyses may have produced exaggerated results because of the small baseline risks involved. To demonstrate this, we replicated the meta‐analysis of four randomized trials of greater than 12‐month follow‐up that made use of a randomized control group not receiving rosiglitazone and reported outcome data for all occurrences of the complementary outcomes (no myocardial infarction, no death from cardiovascular causes, and no heart failure). Data were combined by means of a fixed‐effects model. In the rosiglitazone group, as compared with the control group, the relative risk for no myocardial infarction was 0.997 (95% confidence interval [CI], 0.994 to 1.000), and the relative risk for no death from cardiovascular causes was 1.001 (95%CI, 0.999 to 1.003). Finally, no heart failure had a relative risk of 0.995 (95%CI, 0.993 to 0.998). Rosiglitazone does not seem to have any significant increase in the risk of myocardial infarction or of death from cardiovascular causes associated with its use. Regulatory authorities should revisit this issue of the appropriate measure for reporting of adverse events with low baseline risks as this has implications well beyond rosiglitazone. Copyright © 2014 John Wiley & Sons, Ltd.